Study On The Hidden Policy Behind The Japanese Control In Indonesia - Arif Muzayin Shofwan; Dessy Farantika (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
The Japanese government's occupation of Indonesia kept the substance of the hidden mission. This paper aims to analyze the hidden policies behind the Japanese colonial policies during the colonization of Indonesia. This writing method is a library study by taking various appropriate literature. The results of this study state that the policy of the Japanese colonialists in various fields when colonizing the Indonesian people was an attempt to win the Greater East Asia War. From the implementation of the policies of the Japanese colonialists, it appears that there are advantages and disadvantages. The implementation of favorable policies then received acceptance from the Indonesian people. Meanwhile, the implementation of detrimental policies then met resistance from the Indonesian people. Some of the beneficial Japanese colonial policies included: Indonesian was widely developed throughout Indonesia; Indonesian people are educated to hold positions; the community has equal opportunities in the field of education, and others. Some of Japan's colonial policies were detrimental, including the Indonesian people being obliged to plant crops that could support the war; exploitation of natural resources that causes the Indonesian people to suffer from poverty, hunger, and misery; forced labor or romusha without pay, and others.